Using reissner-nordstrom solution for modeling epileptic seizures - Noraini Ismail, 1963-; Tahir Ahmad, supervisor; Fakulti Sains (2013)
Thesis (Ph.D (Matematik)) - Universiti Teknologi Malaysia, 2013